Magnetic coupling of divalent metal centers in postsynthetic metal exchanged bimetallic DUT-49 MOFs by EPR spectroscopy - Thangavel, Kavipriya; Mendt, Matthias; Garai, Bikash; Folli, Andrea; Bon, Volodymyr; Murphy, Damien M.; Kaskel, Stefan; Poeppl, Andreas (AIP Advances, 2023)
EPR measurements at X- (9.5 GHz), Q- (34 GHz) and W-band (94 GHz) on paddlewheel (PW) type post-synthetic metal exchanged DUT-49(M,M): M- Zn, Mn, Cu MOFs are here reported (DUT-Dresden University of Technology). Temperature-dependent X-band measurements are recorded from T = 7 K to T = 170 K on monometallic DUT-49(Cu), DUT-49(Mn), and bimetallic DUT-49(Cu0.7Zn0.3), DUT-49(Cu0.5Mn0.5) MOFs. In the case of the CuII - CuII dimers in DUT-49(Cu), an isotropic exchange coupling of the metal ions (2J = -240(11) cm-1) determined from the EPR intensity of the S = 1 spin state of the CuII-CuII dimers using the Bleaney Blowers equation. The sign of the found isotropic exchange coupling constant confirms an antiferromagnetic coupling between the cupric ions. Also, the MnII ions in the paddle wheels of DUT-49(Mn) are antiferromagnetically coupled. However, at low temperatures, EPR measurements reveal the presence of CuII and MnII monomers in DUT-49(Cu) and DUT-49(Mn), respectively, either associated with extra framework sites or defective paddle wheels. Otherwise, EPR signals observed for bimetallic DUT-49(Cu0.7Zn0.3) and DUT-49(Cu0.5Mn0.5) MOFs reveal the formation of mixed ion CuII-ZnII and CuII-MnII paddle wheels with SCuZn =1/2 and SCuMn = 2 spin states, respectively.
CRIS-Team Scopus Importer:2023-03-20